Peran perempuan dalam penggunaan alat kontrasepsi - Anis Fitriani (Faculty of Social and Political Science, Universitas Airlangga, 2016)
Family planning is a program established by government to minimize the population explosion by preventing pregnancy and child birth. Women are naturally able to conceive and give birth so they become the target of higher contraceptive use than men. Women in the Pucangro Village Kalitengah subdistrict in Lamongan regency explained their experiences and knowledge they have in using contraception. This type of research is qualitative phenomenology. In this study, researcher explains knowledge and experiences of women in using contraception. Information obtained through observation of women’s life by conducting interview with five women who use contraceptives. Contraception which used by many people in Pucangro Village, Kalitengah subdistrict, Lamongan regency are injection, pill, implant and steady contraception. Women often change contraception methods to adjust the most suitable type for their body because of the effects of contraception make users uncomfortable. Even so, informants persist in using contraception because they have no other choice. Frequency in changing contraceptive method also due to women's knowledge about contraceptive methods which is critically low, such knowledge is mostly gained throughm experiences from parents and siblings. The partner (husband) are less involved and do not want to know the use of contraception’s partner (wife). Several factors that stimulate contraception usage are knowledge possession, level of education, encouragement from family or partner, and side effect of the contraception itself. Women have the power to determine the type of contraception they prefer but no power to refuse using contraception even though negative effects are most likely to occur.